ALIXE: a phase‐combination tool for fragment‐based molecular replacement. Issue 3 (5th March 2020) - Millán, Claudia; Jiménez, Elisabet; Schuster, Antonia; Diederichs, Kay; Usón, Isabel
Abstract : The software ALIXE, which is available as a standalone program as well as integrated into the ARCIMBOLDO programs, combines partial solutions in reciprocal space to increase the signal and reduce the number of intermediate solutions. Its new implementation is faster and can be used by default in the process of phasing with fragments even on modest hardware. Abstract : Fragment‐based molecular replacement exploits the use of very accurate yet incomplete search models. In the case of the ARCIMBOLDO programs, consistent phase sets produced from the placement and refinement of fragments with Phaser can be combined in order to increase their signal before proceeding to the step of density modification and autotracing with SHELXE . The program ALIXE compares multiple phase sets, evaluating mean phase differences to determine their common origin, and subsequently produces sets of combined phases that group consistent solutions. In this work, its use on different scenarios of very partial molecular‐replacement solutions and its performance after the development of a much‐optimized set of algorithms are described. The program is available both standalone and integrated within the ARCIMBOLDO programs. ALIXE has been analysed to identify its rate‐limiting steps while exploring the best parameterization to improve its performance and make this software efficient enough to work on modest hardware. The algorithm has been parallelized and redesigned to meet the typical landscape of solutions. Analysis of pairwise correlation between the phase sets has also been explored to test whether this would provide additional insight. ALIXE can be used to exhaustively analyse all partial solutions produced or to complement those already selected for expansion, and also to reduce the number of redundant solutions, which is particularly relevant to the case of coiled coils, or to combine partial solutions from different programs. In each case parallelization and optimization to provide speedup makes its use amenable to typical hardware found in crystallography. ARCIMBOLDO_BORGES and ARCIMBOLDO_SHREDDER now call on ALIXE by default.